Investigating the impact of digital business ecosystem in enhancing Islamic mobile banking adoption through the TOE framework - Abdurrahman Syahrawi (Digital Business, 2024)
This research investigates how the dimensions of the Technology, Organization, and Environment (TOE) framework influence the digital business ecosystem (DBE) and, in turn, how this ecosystem impacts the adoption of Islamic Mobile Banking (IMB). It addresses a gap in existing literature by adopting a customer-centric perspective, highlighting how DBE affects IMB adoption, a departure from previous studies that primarily focused on internal organizational factors. To achieve its objectives, the study employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data from 985 IMB users in Indonesia. The findings reveal that DBE significantly influences IMB adoption, particularly when moderated by customer behavior as an environmental factor. Factors such as perceived usefulness and ease of use within the technological domain, firm reputation and innovation within the organizational domain, and perceived risk and sharia compliance as environmental factors all positively and significantly impact DBE. Additionally, perceived security has a significant effect on DBE, especially when mediated by perceived ease of use. Furthermore, DBE serves as a crucial mediator between all dimensions of the TOE framework and IMB adoption. This research offers a theoretical contribution by examining the TOE framework dimensions from a customer's perspective, revealing their impact on DBE and IMB adoption. From a managerial perspective, the study provides valuable insights for banks on how to effectively manage technological, environmental, and organizational dimensions to strengthen DBE and promote IMB adoption.
Keywords: 650; Banking performance; Digital business ecosystem; IMB; TOE framework